(untitled) (Biological Sciences - PJSIR, 2010)
Fungi isolated from oil contaminated soils were screened for exogenous lipolytic activity. Optimization of fermentation conditions such as substrate, temperature, pH, moisture content, incubation period, carbon source, nitrogen source and metal ions for maximum lipase production was examined under solid state fermentation by the local isolate of Aspergillus flavus KUF108. Purification of crude enzyme was carried out by ammonium sulphate precipitation, dialysis and DEAE cellulose column chromatography. The lipase was found to be active at pH 5 and 50 °C, and stable between pH 5-6 and 40-60 °C. The apparent molecular weight of purified enzyme was 44 kDa.